2021
DOI: 10.5772/intechopen.96585
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix in Cardiac Tissue Mechanics and Physiology: Role of Collagen Accumulation

Abstract: The extracellular matrix (ECM) forms a mesh surrounding tissue, made up of fibrous and non-fibrous proteins that contribute to the cellular function, mechanical properties of the tissue and physiological function of the organ. The cardiac ECM remodels in response to mechanical alterations (e.g., pressure overload, volume overload) or injuries (e.g., myocardial infarction, bacterial infection), which further leads to mechanical and functional changes of the heart. Collagen, the most prevalent ECM protein in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 162 publications
(214 reference statements)
0
4
0
Order By: Relevance
“…This is consistent with the prior report of collagen content in human LV and RV determined from hydroxyproline assays ( Miles et al, 2020 ). Second, although type I collagen is the most abundant type of collagen in ventricles ( LeBar and Wang, 2021 ), the type III collagen content was significantly correlated with the M L in all ventricles and at low strains ( Figure 7B , p < 0.05). This indicates that the longitudinal elasticity partly stemmed from type III collagen recruitment.…”
Section: Discussionmentioning
confidence: 94%
“…This is consistent with the prior report of collagen content in human LV and RV determined from hydroxyproline assays ( Miles et al, 2020 ). Second, although type I collagen is the most abundant type of collagen in ventricles ( LeBar and Wang, 2021 ), the type III collagen content was significantly correlated with the M L in all ventricles and at low strains ( Figure 7B , p < 0.05). This indicates that the longitudinal elasticity partly stemmed from type III collagen recruitment.…”
Section: Discussionmentioning
confidence: 94%
“…A tightly controlled ECM turnover is necessary for normal protein function and relies on the balance between ECM synthesis and degradation [47]. When ECM turnover is disturbed, factors that contribute to the synthesis or degradation of ECM proteins will trigger acute or chronic tissue remodeling, changing the structure and mechanical function of the ECM [47].…”
Section: Collagen Types I and Iiimentioning
confidence: 99%
“…Previous studies indicated that transforming growth factor-β (TGF-β) activation is associated with the development of CVD [48,49]. Under normal physiological circumstances, TGF-β contributes to a healthy vessel wall structure through the control of ECM protein synthesis and deposition [47]. A potential mechanism could be increased activation of TGF-β in the high-CV risk group, which may consequently lead to an increase in type I and III collagen deposition in the ECM and therefore lower excretion of these collagen peptides.…”
Section: Collagen Types I and Iiimentioning
confidence: 99%
“…Right ventricle (RV) failure is common in the advanced stages of pulmonary hypertension and is a useful predictor of mortality in these patients . In the process of chronic pressure overload, the failing RV becomes stiffer, more anisotropic, , and undergoes global capillary rarefaction, leading to myocardial inefficiency. Unlike hypertensive remodeling in the left ventricle (LV), capillary rarefaction plays a critical role in hypertensive RV maladaptation, , and thus pro-angiogenic strategies could potentially offer a RV-specific therapy.…”
Section: Introductionmentioning
confidence: 99%